Epidemiological Characterization of Fatal Head Trauma in Cartagena, Colombia, 2007-2011 (2016)
Introduction: fatal head trauma is a common in our environment, and there are no reliable statistics on the actual frequency. Methodology: A retrospective escriptive study was conducted, based on the records of the National Institute of Legal Medicine and Forensic Sciences of the Basic Unit of Cartagena, Colombia. Results: mortality rates ranged from 7-14 / 100,000 inhabitants / year during the period analyzed, with more frequently occurrence in males, in a ratio ranging from 25:1 in the first year studied, 10:1 at the end of the period and in ages from 20 to 35 years. The cause thereof included perforating wounds by firearm projectiles in 56.8 % of cases, followed by injuries in traffic accident in 32.4 % of the cases, with supratentorial localization injuries in 82.8 % of the cases. 69.9 % of the victims died at the scene, affecting individuals between 20 and 35 years old. Georeferencing of cases allowed to observe that the communes with the highest rates reported were 1, 4 and 11, corresponding to the Histórica, Caribe Norte communes, and the areas of La Virgen and Turística. Conclusions: The fatal head trauma is frequent in the city, among male individuals aged 20 to 35 years, mostly due to gunshot wounds, homicide, followed by traffic accidents. It is necessary to delve into the facts related to these results.